Biodiversidade de parasitas de peixes da família Loricariidae (Teleostei: Siluriformes) procedentes do rio Sapucaí-Mirim, Brasil - Franceschini, Lidiane [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Loricariid fishes (Siluriformes) presents great intraspecific phenotypic plasticity throughout their ontogeny. The limited knowledge about the biological aspects, biogeographic patterns of distribution and high morphological variability of these fishes make the studies on biodiversity of this group difficult, including that about parasites. Therefore, the aim of this study was to survey the biodiversity of parasites of Loricariidae fishes from an area under the influence of the construction of Small Hydro Power Plants (SHPPs) in the Sapucaí- Mirim River, São Paulo State, Brazil. Moreover, the study evaluated the structure of parasitic communities of these hosts (at both the component community and infracommunity levels), assessing the possible variation in infracommunity abundance among sites and fish species based on explanatory variables (spatial, temporal, and host traits). During 2012 and 2013, two annual samples (dry/rainy seasons) were carried out, in eight sampling sites situated in the reservoirs of three SHPPs: Palmeiras, Anhanguera, and Retiro. Specimens of Loricaria prolixa, Hypostomus regani, Hypostomus ancistroides, Hypostomus strigaticeps, Hypostomus heraldoi, Hypostomus margaritifer, Hypostomus cf. margaritifer; Hypostomus topavae; Hypostomus aff. topavae and Hypostomus sp., were analyzed, totaling 334 fishes. Twenty-nine taxa were found, totaling 15,957 parasite specimens, and Monogena was the dominant group, which showed the greatest richness (13 taxa). The parasites were identified as follows: monogeneans Dactylogyridae, Gyrodactylidae and Microcotylidae in the gills and skin. Seven new monogenean species were found, belonging to Demidospermus, Trinigyrus and Heteropriapulus genera. Austrodiplostomum sp. metacercariae in the vitreous humor and celomatic cavity, and an unidentified metacercariae encysted in the liver and intestine (Trematoda). For Nematoda it was observed: Rhabdochona sp. (Rhabdochonidae), larvae of Procamallanus (Spirocamallanus) sp. and adults of Procamallanus (Spirocamallanus) inopinatus (Camallanidae); third-stage larvae of Contracaecum sp. (Anisakidae) and larvae and adult of unidentified nematodes (Nematoda gen. sp.). Besides helminths, Glossiphonidae hirudineans were found in skin, fins and oral cavity, infesting all the fish species, and mixozoans of the genus Myxobolus, parasitizing gills of H. ancistoides. Multivariate Regression Trees (MRT) were performed in order to verify the relative effects and interactions of factors related to the host traits (host species, body weight, and relative condition factor - Kn), temporal (season and year of capture) and environmental (sampling sites) on the abundance of parasite assemblage at several scales context (global, genus, and local scales). The effects caused by differences between host species were a determinant predictor on the parasite abundance of loricariids (global, genus “Hypostomus”, and local scales), and L. prolixa presented a greatest difference in the composition and abundance of their parasites in relation to Hypostomus spp.. Therefore, the spatial structure of the infracommunities evaluated was determined, especially, by the intrinsic differences among host species and by the structural complexity of the sampling areas assessed.

Peixes da família Loricariidae (Siluriformes) apresentam grande plasticidade fenotípica intraespecífica durante toda sua ontogenia. O conhecimento limitado sobre os aspectos biológicos, padrões biogeográficos e elevada variabilidade morfológica destes peixes dificultam estudos sobre a biodiversidade acerca deste grupo, incluindo estudos sobre a fauna parasitária. Assim, o objetivo deste estudo foi realizar levantamento da biodiversidade de parasitas de peixes da família Loricariidae em áreas sob a influência da construção de Pequenas Centrais Hidrelétricas (PCHs) no rio Sapucaí-Mirim, Estado de São Paulo, Brasil. Ademais, avaliar a estrutura das comunidades parasitárias dos hospedeiros analisados (ao nível de infracomunidade e comunidade componente) e possíveis mudanças na abundância das infracomunidades baseadas em variáveis explanatórias (espaciais, temporais e fatores intrínsecos ao hospedeiro). Para tanto, durante os anos de 2012 e 2013 foram realizadas duas amostragens anuais (período seco/chuvoso), em oito áreas amostrais situadas nos reservatórios de três PCHs: Palmeiras, Anhanguera e Retiro. Foram necropsiados 334 loricarídeos pertencentes a 10 espécies: Loricaria prolixa, Hypostomus margaritifer, Hypostomus heraldoi, Hypostomus strigaticeps, Hypostomus regani, Hypostomus ancistroides, Hypostomus cf. margaritifer, Hypostomus topavae, Hypostomus aff. topavae, além de uma espécie não identificada pertencente ao gênero Hypostomus. Foram encontrados 29 taxa de parasitas, totalizando 15.957 espécimes, sendo a classe Monogenea a com maior riqueza (13 taxa). Os parasitas observados foram: monogenéticos das famílias Dactylogyridae nas brânquias, Gyrodactylidae nas brânquias e pele (muco) e Microcotylidae na pele (muco). Sete novas espécies de monogenéticos foram encontradas, pertencendo aos gêneros Demidospermus, Trinigyrus e Heteropriapulus. Metacercárias de Austrodiplostomum sp. nos olhos e cavidade celomática e metacercárias de digenéticos encistadas nas brânquias, cavidade ocular, cristalino, serosa do fígado e intestino (Trematoda). Dentre os nematoides foram encontrados Rhabdochona sp. (Rhabdochonidae), larvas de Procamallanus (Spirocamallanus) sp., adultos de Procamallanus (Spirocamallanus) inopinatus (Camallanidae); larvas de terceiro estádio (L3) de Contracaecum sp. (Anisakidae) e larvas e adulto de nematoides não identificados (Nematoda gen. spp.). Além dos helmintos, foram encontrados hirudíneos da família Glossiphoniidae, na pele, nadadeiras e cavidade bucal, acometendo todas as espécies de loricarídeos e mixozoários do gênero Myxobolus em brânquias de H. ancistroides. Árvores de Regressão Multivariada (MRT) foram produzidas para verificar os efeitos relativos e interações de fatores relacionados aos hospedeiros (espécie, peso, fator de condição relativo), fatores temporais (estação e ano de captura) e ambientais (local de coleta) sobre a abundância dos parasitas em diferentes escalas de contexto (global, gênero do hospedeiro e local). Os efeitos causados pelas diferenças entre as espécies hospedeiras foram preditores determinantes sobre a abundância parasitária (escalas global, gênero “Hypostomus” e local) e L. prolixa apresentou a maior diferença na composição e abundância de seus parasitas em relação a Hypostomus spp.. A estrutura espacial das infracomunidades de parasitas dos loricarídeos avaliados foi determinada, sobretudo, pelas diferenças entre fatores intrínsecos relacionados as espécies hospedeiras, bem como pela distribuição dos hospedeiros e complexidade estrutural das áreas nas quais foram amostrados.
Biodiversity of parasites of Loricariidae fishes (Teleostei: Siluriformes) from Sapucaí-Mirim River, Brazil
Keywords: Catfishes; Freshwater fishes; Ectoparasites; Endoparasites; Small Hydroeletric Power Plants; Multivariate Regression Trees; Pequenas Centrais Hidrelétricas; Árvore de Regressão Multivariada; Cascudos; Peixes dulcícolas; Ectoparasitas; Endoparasitas